Functional Neurocircuits and Neuroimaging Biomarkers of Tobacco Use Disorder. Issue 2 (February 2018) - Sutherland, Matthew T.; Stein, Elliot A.
Abstract : Drug abuse and addiction remain major public health issues, exemplified by the opioid epidemic currently devastating the United States. Treatment outcomes across substance use disorders remain unacceptably poor, wherein drug discovery/development for this multifaceted neuropsychiatric disorder focuses on single molecular-level targets. Rather, our opinion is that a systems-level neuroimaging perspective is crucial for identifying novel therapeutic targets, biomarkers to stratify patients, and individualized treatment strategies. Focusing on tobacco use disorder, we advocate a brain systems-level perspective linking two abuse-related facets (i.e., statelike withdrawal and traitlike addiction severity) with specific neurocircuitry (insula- and striatum-centered networks). To the extent that precise neurocircuits mediate distinct facets of abuse, treatment development must adopt not only a systems-level perspective, but also multi-intervention rather than mono-intervention practices. Highlights: One reason for low smoking quit rates is a still limited appreciation of the neurocircuitry underlying distinct aspects of TUD. Neuroimaging is providing enhanced insight into the multifaceted nature of TUD by considering activity within and interactions between brain regions. We highlight emerging distinctions between neurocircuitry underlying two facets of the TUD, namely, those linked to statelike pharmacological factors (withdrawal related) and to traitlike addiction severity factors (addiction related). An emerging concept is that insula-centric neurocircuit dynamics may represent a statelike biomarker of acute withdrawal and that dynamics between the anterior cingulate cortex and striatum represent a traitlike biomarker of chronic addiction severity. Pharmacologically targeting both neurocircuits simultaneously may improve outcomes.